PERAN KEPALA SEKOLAH SEBAGAI SUPERVISI DALAM MENINGKATKAN KINERJA GURU DI SMPN 18 KABAENA UTARA KABUPATEN BOMBANA - Vadillah, Agnes; Akil, M.; Razaq, Ahmad; Mustamin, Mustamin; Raehana, Syarifa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the role of the principal as a supervisor in improving teacher performance at SMP Negeri 18 Kabaena Utara, Bombana Regency. The purpose of this research was to describe the implementation of supervision, identify teacher performance, and analyze how the principal performs a supervisory role to improve teacher performance. This study used a qualitative descriptive method. The data were collected through observation, interviews, and documentation involving the principal, vice principal, and teachers, while secondary data were taken from attendance records, archives, and school documentation. The findings show that the supervision program is carried out through planning, organizing, and utilizing supervision results. In its implementation, the principal is assisted by senior teachers, and each stakeholder is given a clear job description as part of the work mechanism. Teacher performance at the school is generally good, with learning activities that are active, innovative, creative, and enjoyable. However, some teachers still need improvement in preparing learning plans and maintaining discipline in class time. The supervision process is applied through direct and indirect approaches to support continuous improvement in teacher professionalism.